HUBUNGAN KOMPETENSI ERA INDUSTRI 4.0, BEBAN KERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIORDAN KINERJA KARYAWAN - Suri Rama Caressa (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
PDAM Kabupaten Sleman’s efforts to improve the organization cannot be separated from good human resources in it, especially in responding the challenges in the era of industrial revolution 4.0. The aim of study to analyze the correlation of competencies, workload, organizational citizenship behavior, and employee performance. The analysis technique used product moment correlation method. The analysis result show that competence has a significant relationship with employee performance. Workload has a significant relationship with employee performance. Organizational citizenship behavior has a significant relationship with employee performance. Competencies, workload, organizational citizenship behavior simultaneusly have a significant influence on employee performance, its 64,1 %.